Draft Annual Plan 1979-80 Government of Maharashtra - Planning Commission (Planning Commission, 1979)
Cost of materials to be received in kinds during 1979-80 has not yet been indicated by the Government of India Outlays for 1978-79 includes committed level of operational cost at the end of 1978-79.
Planning Department
Government of Maharashtra Planning Department